2017
DOI: 10.5116/ijme.5740.2b7a
|View full text |Cite
|
Sign up to set email alerts
|

Does team-based learning improve performance in an infectious diseases course in a preclinical curriculum?

Abstract: Objectives: To examine whether introduction of Teambased Learning (TBL) improves student learning resulting in improved performance on final examination questions and decreased failures in an infectious diseases course. Methods: To improve mastery of course content, we designed an intervention, which provided weekly TBL exercises in study years 2 and 3 to review concepts presented during didactic lectures and laboratory exercises. The remaining course structure and content was essentially unchanged. All studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Each student on a TBL team shares the gRAT score independent of their individual contributions to the team discussion. As expected, average gRAT scores are generally higher than average iRAT scores .…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Each student on a TBL team shares the gRAT score independent of their individual contributions to the team discussion. As expected, average gRAT scores are generally higher than average iRAT scores .…”
Section: Introductionsupporting
confidence: 76%
“…Previously, we have reported success of this method in improving outcomes for poorly performing students . More recently, we have shown that TBL is an excellent predictor of student success in a first year Infectious Diseases course at our institution . We have also shown that replacement of engaged lectures with more TBL exercises in a pipeline course for underrepresented in medicine (URM) students significantly ( p < 0.01) improved performance on the final examination .…”
Section: Introductionmentioning
confidence: 69%
“…TBL has been shown to disproportionately help those students who are struggling most with course material (20). Additionally, our group has shown that the introduction of TBL exercises to a first-year medical school course improved student final-examination performance in addition to reducing the number of course failures, also suggesting that TBL mainly helps struggling students (4). Thus, we hypothesized that increased use of active learning exercises, such as TBL, would improve understanding of course content as assessed by performance on an end-of-course examination in the Medical Microbiology course of the PULSE program.…”
Section: Introductionmentioning
confidence: 84%
“…Thus, it appears that this modest incentive may have been sufficient for some to improve their performance in the TBL. Interestingly, our first-year medical students resented the grading of the Application exercise and felt that this practice increased student anxiety (4). Perhaps the use of external incentives other than grading may be a future direction for investigation into alternative ways to provide external motivation without increasing student anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The research results indicate that students improved their understanding of content in TBL classes and that lower-achieving students benefited the most from this particular teaching approach [18][19][20][21]. Students reported positive feedback and performed better in groups than as individuals in TBL classes [22].…”
Section: Introductionmentioning
confidence: 85%